Food : - Coultate, T. P. (Royal Society of Chemistry, 2009)
As a source of detailed information on the chemistry of food, this book is without equal. It investigates components which are present in large amounts (carbohydrates, fats, proteins, minerals and water) and also those that occur in smaller quantities (pigments, flavours, vitamins and preservatives). The fifth edition has been extensively rewritten to bring it right up to date and a number of new topics have been introduced. New features include: (1) Topics of particular interest to specialist readers or more advanced students have been moved to a Special Topics section at the end of each chapter; (2) An exhaustive index and the structural formulae of more than 600 food components are given; (3) Features a comprehensive listing of recent, relevant review articles as well as books for further reading; (4) The nutritional significance of food components is indicated at every stage without attempting to usurp the role of explicitly nutrition texts; (5) Total updating in all chapters including legislative changes with many new diagrams and almost all others completely redrawn; (6) Frequent references, where appropriate, to wider issues, e.g. the evolutionary significance of lactose intolerance, fava bean consumption and malaria, rain forest destruction